Pengendalian Kualitas Serbuk Kayu Menggunakan Metode Seven Tools dan FMEA - Mahmud, Minhajun Ni'am; Dewi, Sinta; Kurniawan, Wahyu (Universitas Muhammadiyah Sorong, 2025)
The rapid development of the industry requires companies to always maintain the quality of each production, production quality control is an important aspect in the production process. PT XYZ is a company engaged in manufacturing that focuses on the production of wood pellets. The problems faced by the company at this time are the factors that cause defects in wood powder products resulting from the wood pellet production process, so it is necessary to improve the quality of wood powder products. Types of defects that may occur include non-uniform particle size defects, high moisture content defects, dirt or foreign object defects. This study was conducted with the aim of identifying potential solutions to reduce defects in wood powder products produced from the wood pellet production process using the seven tools method used to identify the causes of defects in the production process and the failure mode and effects analysis (FMEA) method used to make improvement efforts. From the results of the seven tools data processing, the highest defect in wood powder is 40% for non-uniform particle size, then the RPN value will be calculated to determine urgent improvement proposals. In the results of the RPN calculation, the highest value was obtained at 240 with a high moisture content defect with proposed improvements to conduct training on drying techniques and the use of MC tools.